IMPACT OF CROPPING PATTERN ON BIOMASS PRODUCTIVITY AND FARMING COMMUNITY OF COLD DESERT AGRO ECOSYSTEM OF HIMACHAL PRADESH - POONAM; RAJAN BAWA (The Bioscan, 2020)
The present investigation was conducted during 2011 to 2013 to study the impact of cropping pattern on biomass production and farming community of cold desert agro ecosystem of village Goshal, located in Lahaul and Spiti district of Himachal Pradesh, India. Study was carried out by dividing the agro ecosystem into nine different grids for sampling following quadrate method. We calculated the Biomass production and input output ratio of traditional crop (barley) and cash crops (potatoes and peas) and found major differences between the two. Potato showed the maximum total above ground and belowground biomass (3.50 kg/m 2 ), pea (4.42 kg/m 2 ) and least was found for barley (1.66 kg/m 2 ). Input output ratio for potato was 1:3.47 with total inputs and 1:6.12 without labour and FYM cost. The input and output ratio for pea crop was 1: 2. 43 including all the inputs and it was 1:4.76 if labour and FYM cost is excluded which is still higher than potatoes. For barley it was 1:1.29 (if labour and FYM cost is added), hence less profitable than cash crops. Thus biomass productivity and economic gains through traditional crops was lower with lower profits to the farming community.